Factors Related to Physician Burnout and Its Consequences: A Review - Patel, Rikinkumar S.; Bachu, Ramya; Adikey, Archana; Malik, Meryem; Shah, Mansi (Behavioral sciences, 2018)
Physician burnout is a universal dilemma that is seen in healthcare professionals, particularly physicians, and is characterized by emotional exhaustion, depersonalization, and a feeling of low personal accomplishment. In this review, we discuss the contributing factors leading to physician burnout and its consequences for the physician’s health, patient outcomes, and the healthcare system. Physicians face daily challenges in providing care to their patients, and burnout may be from increased stress levels in overworked physicians. Additionally, the healthcare system mandates physicians to keep a meticulous record of their physician-patient encounters along with clerical responsibilities. Physicians are not well-trained in managing clerical duties, and this might shift their focus from solely caring for their patients. This can be addressed by the systematic application of evidence-based interventions, including but not limited to group interventions, mindfulness training, assertiveness training, facilitated discussion groups, and promoting a healthy work environment.